LADCP current profiles collected during Med-SHIP cruise TAlPro2022 - Katrin Schroeder (PANGAEA, 2023)
This data set contains station data of top-to-bottom oceanic current measurements performed with Lowered Acoustic Doppler Current Profilers (LADCP) during the Med-SHIP cruise TAlPro2022 (Chief Scientist: Katrin Schroeder; Toulone - La Spezia, RV Belgica, 17/05/2022 - 26/05/2016). The LADCP devices in use were a downward and an upward-looking ADCP of type Teledyne RDI Workhorse Monitor 300 kHz. Station data of zonal and meridional oceanic velocities are reported in [cm/s] on a 4 m vertical grid. The processing of the data has been done using the LDEO LADCP data processing software (Thurnherr et al., 2010).